Predicting Student Success in Online Physical Education. Issue 1 (2nd January 2021) - Goad, Tyler; Jones, Emily; Bulger, Sean; Daum, David; Hollett, Nikki; Elliott, Eloise
ABSTRACT: Currently, limited data are available on student retention rates and attrition factors in online physical education (OLPE) courses. Several early OLPE studies as well as the 2007 NASPE Initial Guidelines for Online Physical Education have suggested that certain prescreening efforts be in place prior to student enrollment in OLPE; however, at present no such empirically sound and theoretically based screening instruments exist. The purpose of the study is to identify online student cognitive characteristics and environmental factors associated with success and/or failure within college online health-related fitness (HRF) courses. Students (N = 821) enrolled in a 16-week online HRF course at a university during the Fall 2017 participated in the study. Data were collected at the beginning of the course with two previously validated research instruments, the Educational Success Prediction Instrument Version-2 (ESPRI-V2) and the Distance Learning Survey (DLS). Results reveled a relationship between course completion and six variables: GPA, class standing, hours worked outside of school, achievement, organization and study environment). The full model containing all predictors was statistically significant (χ 2 (6, N = 821) = 94.296, p <.001), indicating that the model was able to distinguish between students who completed and did not complete the online course. This analysis provides an initial understanding of the unique student characteristics affecting OLPE course completion.